Morpho-Physiological Adaptations of Drought-Resilient and Susceptible Brassica napus Genotypes to Sulphur-Coated Urea Fertilization - Zafar, Ibtesam; Khan, Nanak; Khan, Nasir Mehmood; Muhammad Khalid; Muhammad Kashif; Mujtaba, Ghulam; Waqas, Khuram; Saeeda Naz; Khan, Muhammad Amaid; Khan, Haider Hayat (Indus Journal of Bioscience Research, 2024)
This study focuses on screening drought-tolerant and sensitive genotypes of Brassica napus L. (an important oilseed crop in Pakistan) and investigates their morpho-physiological responses to sulphur-coated urea (SCU) under drought conditions. Genotypes were categorized into highly drought tolerant (HDT), moderately drought tolerant (MDT), and highly drought sensitive (HDS) through hierarchical cluster analysis. Out of 100 genotypes, 20 were HDT, 30 were MDT, and 50 were HDS. Three genotypes from each category were subjected to two drought levels (80% field capacity and 50% field capacity) and were treated with SCU, urea, or no nitrogen. Key parameters such as leaf relative water content, chlorophyll content, excised leaf water loss, and membrane stability index (MSI) were recorded. Drought-tolerant genotypes performed well in both germination and seedling stages, showing higher excised leaf water loss, relative water content, chlorophyll values, seed weight, and yield-related traits. Initially, five concentrations of PEG-6000 (5% to 25%) were tested to determine optimal levels for screening drought tolerance. Results showed that 25% PEG-6000 induced 50% drought injury index (DII), making it the most promising concentration. Various morpho-physiological traits such as germination rate, shoot/root length, fresh and dry weight, and drought tolerance indices were assessed. The study concluded that drought-tolerant genotypes responded positively to SCU application, making them suitable for cultivation in water-scarce regions of Pakistan.